TRAPOFLE: uma proposta de ferramenta online de tradução pedagógica do português brasileiro para o francês língua estrangeira - Azevedo, Eryka Natasha Bandeira (2024)
The evolution of educational technologies has created new opportunities for foreign language teaching, expanding available resources and facilitating learning. In this context, pedagogical translation emerges as an interesting methodological approach, not only aiding in the deve- lopment of linguistic skills but also contributing to a deeper understanding of the culture of the countries where the taught languages are spoken. To explore and enhance these benefits, this study presents a proposal for an online technological translation tool, envisioned to be called TRAPOFLE (Translation from Brazilian Portuguese to French as a Foreign Language), aimed at supporting French learning for Brazilian Portuguese speakers. This proposal is grounded in translation and seeks to integrate the functionalist principles of Nord (1991, 2012) into pedago- gical practice. By adopting this perspective, the proposed tool aims to encourage learners to consider the functions and contexts of language, promoting translation that respects the cultural and linguistic specificities of both languages. Although this study does not include the technical implementation of the online tool, it aims to develop a model that will, in the future, serve as a theoretical framework for the creation of the software itself. To this end, our study will focus on the following topics: translation from French to Brazilian Portuguese (specific characteris- tics and pedagogical impacts); the functionalist perspective of translation; and pedagogical translation. Based on the discussion of these topics, we will propose a model aimed at enriching French language learning by ensuring that learners take into account its specificities, as well as those of Brazilian Portuguese. Our proposal intends to include essential aspects such as the specific characteristics of translation from French to Brazilian Portuguese and the pedagogical impacts of this practice. The TRAPOFLE proposal seeks not only to lay the foundation for creating a tool that facilitates French language learning but also to support educators through activities involving translation, contributing to the training of competent translators capable of recreating texts with critical awareness and intercultural sensitivity. These translators will be attentive to structural changes, the complexity of translation, negotiating between source and target languages, and understanding the possible inequalities between texts, authors, and lin- guistic systems.